Practical possibilities of blood grouping for parentage information: A pilot study in Zaire - Thorpe, W.R.; D'Ieteren, G.D.M.; Feron, A.; Mundia, M.; Ross, D.; Sheria, M.; Spooner, R.L.; Trail, J.C.M. (ILCA/ILRAD, 1988)
Studies the effectiveness of the blood grouping technique for parentage identification of cattle at the Mvuazi research station, Bas-Zaire, Zaire.